Subsistence harvest of beluga or white whales (Delphinapterus leucas) in northern and western Alaska, 1987–2006 - Frost, Kathryn J.; Suydam , Robert S. (J. Cetacean Res. Manage., 2023)
Four stocks of beluga or white whales (Delphinapterus leucas) are hunted by Alaska Natives in northern and western Alaska. These are the Beaufort Sea, eastern Chukchi Sea, eastern Bering Sea and Bristol Bay stocks. Since 1987, the Alaska Beluga Whale Committee has monitored the subsistence harvests of belugas from these stocks. During this 20 year period, the total landed harvest for the four stocks combined (adjusted for years with missing data) ranged from 208 in 1995 to 494 in 1988, with a 20 year average of 323 per year. For individual stocks the average annual landed harvests for 1987–2006 were: Beaufort Sea – 41; Chukchi Sea – 62; eastern Bering Sea – 191; and Bristol Bay – 20. There was no significant longterm trend (p>0.05) in the rate of harvesting for any stock from 1987–2006. Average landed harvests relative to estimated stock size were: 0.1% for the Beaufort Sea (0.4% including belugas harvested from the Beaufort Sea stock by Canadian hunters); 1.7% for the eastern Chukchi Sea; 1.1% for the eastern Bering Sea; and 1.1% for Bristol Bay. The success of beluga harvest monitoring in Alaska is due to the cooperation of beluga hunters from more than 40 small coastal communities who report their harvests to the Alaska Beluga Whale Committee (ABWC). Through the ABWC, beluga hunters have been able to formalise their role in managing their subsistence resources.